2005
DOI: 10.1007/s11250-005-5688-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Fasciola gigantica and Amphistomes in Cattle on Traditional, Small-scale Dairy and Large-scale Dairy Farms in the Southern Highlands of Tanzania

Abstract: A longitudinal descriptive study was conducted to determine the prevalence and distribution of flukes (Fasciola gigantica and amphistomes) on traditional, large-scale and small-scale dairy cattle farms in Iringa district, southern highlands of Tanzania. Coprological examinations of different cohorts for the presence of fluke eggs were recorded monthly. Results indicated a significant influence of the type of management on the prevalence of both Fasciola and amphistomes. The prevalence of flukes was highest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
67
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 3 publications
13
67
0
4
Order By: Relevance
“…The nutritional deficiency, grazing habits, immunological status, pasture management, presence of intermediate host and vector and the number of infective larvae and eggs in the environment act as predisposing factors [5]. According to [6], loss in body weight, poor reproductive performance, digestive disturbance, and emaciation for longer period result from the gastro-intestinal parasites. They can also lead to anaemia due to the production of toxins.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional deficiency, grazing habits, immunological status, pasture management, presence of intermediate host and vector and the number of infective larvae and eggs in the environment act as predisposing factors [5]. According to [6], loss in body weight, poor reproductive performance, digestive disturbance, and emaciation for longer period result from the gastro-intestinal parasites. They can also lead to anaemia due to the production of toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Iringa region, forming part of the southern highlands, is known to be a trematode-endemic area, especially for Fasciola gigantica and amphistomes (Mahlau 1970;Makundi 2001;Keyyu et al 2005a) and gastrointestinal (GI) nematodes are also highly prevalent and widespread (Keyyu et al 2005a(Keyyu et al , b, 2006). An abattoir survey conducted in Iringa district of Iringa region showed that almost all indigenous cattle (97.2%) examined at the abattoir harboured GI nematodes (Keyyu et al 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…An abattoir survey conducted in Iringa district of Iringa region showed that almost all indigenous cattle (97.2%) examined at the abattoir harboured GI nematodes (Keyyu et al 2003a). Epidemiological studies conducted in the region have shown that helminth infections reveal distinct seasonal patterns with a peak of GI nematodoses during the rainy season (Keyyu et al 2005b); and high prevalences of fasciolosis and amphistomosis towards the end of the dry season and the early part of the rainy season (Makundi 2001;Keyyu et al 2005a). A study on worm control practices and anthelmintic usage in the region showed that anthelmintic usage was irrational, treatments being based on availability of money to buy drugs and not the epidemiology of parasites in the area (Keyyu et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…En raison de la chronicité de leurs manifestations cliniques, les helminthiases peuvent apparaî-tre comme dotées d'un pouvoir pathogène limité alors que leurs prévalences et leur action prolongée dans le temps pénalisent lourdement la productivité des éle-vages (Maichomo et al, 2004). Parmi les trématodes africains, les caractéristiques épidémiologiques du genre Fasciola sont bien connues (Keyyu et al, 2005) de même que celles de Schistosoma bovis (Sonsino, 1876), espèce qui a fait l'objet d'études approfondies en Afrique de l'Est (Kassuku et al, 1986a ;Majid et al, 1980). En parallèle, grâce à l'utilisation de méthodes isotopiques (Saad et al, 1984a), la pathogénie de S. bovis chez les bovins est clairement établie, le passage transpariétal des oeufs intestinaux étant la source première che de S. curassoni fut extraite à partir de deux moutons abattus dans la même région et maintenue sur Bulinus umbilicatus.…”
Section: Matériel Et Méthodesunclassified